1977
DOI: 10.1128/iai.16.3.898-903.1977
|View full text |Cite
|
Sign up to set email alerts
|

Properties of density gradient-fractionated peripheral blood leukocytes from cattle infected with bovine leukemia virus

Abstract: Discontinuous bovine serum albumin gradients were used to fractionate peripheral blood leukocytes from bovine leukemia virus (BLV)-free and BLV-infected cows. The release of infectious BLV and spontaneous incorporation of [3H]thymidine were not properties of density gradient-fractionated leukocytes from a BLV-free cow. When leukocytes from BLV-infected cattle were fractionated, B lymphocytes which spontaneously incorporated [3H]thymidine could be separated as a distinct subpopulation from B lymphocytes which r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1984
1984
1998
1998

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Spontaneous proliferation of PBMC from persistently lymphocytotic BLV-infected cows is IL-2 and viral antigen dependent. PBMC from persistently lymphocytotic cows spontaneously incorporate [ 3 H]thymidine when placed in culture, predominantly due to proliferation of B lymphocytes (27,28). In 14 individual experiments, spontaneous [ 3 H]thymidine uptake of PBMC from persistently lymphocytotic cows was 2.5 to 50 times that of uninfected cows measured in the same assay (combined data presented in Fig.…”
Section: Resultsmentioning
confidence: 85%
“…Spontaneous proliferation of PBMC from persistently lymphocytotic BLV-infected cows is IL-2 and viral antigen dependent. PBMC from persistently lymphocytotic cows spontaneously incorporate [ 3 H]thymidine when placed in culture, predominantly due to proliferation of B lymphocytes (27,28). In 14 individual experiments, spontaneous [ 3 H]thymidine uptake of PBMC from persistently lymphocytotic cows was 2.5 to 50 times that of uninfected cows measured in the same assay (combined data presented in Fig.…”
Section: Resultsmentioning
confidence: 85%
“…According to some reports, since surface immunoglobulin-positive (SIg') cells increase in EBL cattle, these tumour cells are of the B-cell lineage (1,6,17,18). O n the contrary, another report showed that peripheral blood lymphocytes (PBL) of cattle with EBL showed a decrease in SIg' cells (10).…”
Section: Introductionmentioning
confidence: 99%
“…1985). In contrast to the HTLVs, however, B-cells are the principal target of BLV infection (Kenyon & Piper 1977b).…”
Section: Introductionmentioning
confidence: 99%